Invisible totalitarianisms and identity crisis in the twenty-first century (Cultura Económica, 2022)
This article is a written version of the lecture given in the forum Challenges for The New Generation 2022. From the general positive opinion about democracy in today´s world, inquiries about its basis. It mentions how from the relativism that is proposed by some authors and a controversial conception of respect of difference appear metaphysical and psychological conditions for the crisis of identity and a totalitarian domination that nowadays is not easily identifiable.
Keywords: DEMOCRACY; RELATIVISM; IDENTITY; TOTALITARIANISM